The Impact of Climate on Economic Growth in Malaysia - Rahim, Shafinah; Guan Puay, Tay (Journal of Advanced Research in Business and Management Studies, 2020)
This study investigates the relationship between factors representing climate change and economic growth in Malaysia, between years 1983 and 2013. The selected varibles include precipitation (mm), temperature(?C) and arable land (% of land used). The objective of this paper is to understand the siginificance of precipitation, temperature and arable land, towards gross domestic product (current LCU). The methodologies employed are Augmented Dickey-Fuller (ADF) unit root test, Dickey-Fuller GLS (DF-GLS) unit root test, the Johansen-Juselius Cointegration test, Vector Error Correction Model (VECM) test, the Variance Decomposition (VDC) test and the Impulse Response Function (IRF) test. The empirical results imply one cointegrating vector between variables, indicating a unidirectional causality long term relationship between precipitation, temperature and arable land towards GDP. Precipitation appears to be the most exogenous variable whereas Temperature the most endogenous at a 50 year horizon period. The IRF test concludes that the variables in this model are able to recover from shocks caused by another variable within 5 years. The relatively short revival period helps government to monitor the progress made by ongoing strategies. Several policies are recommended for the benefit of the relevant government authorities in dealing with the current climate crisis which will inevitably affect the Malaysian economic growth.